Inovasi Pemanfaatan Limbah Pupuk Kandang Sapi dan Mikoriza dalam Meningkatkan Hasil Panen Jagung Manis Di Moncok Karya, Ampenan - Astiko, Wahyu; Fauzi, Mohamad Taufik; Sudirman, Sudirman; Ernawati, Ni Made Laksmi; Muthahanas, Irwan (Jurnal Gema Ngabdi, 2025)
The issue of low sweet corn yields and the underutilization of organic waste highlights the need for sustainable agricultural innovation. This community service program aimed to introduce and apply the use of cow manure waste enriched with mycorrhizae to improve sweet corn yields in the "Karya Usaha Bersama" farmer group, Moncok Karya, Ampenan. The program was implemented using an andragogical approach (Adult Education Method), consisting of: (1) education on the benefits and application of mycorrhiza-based cow manure (20% theory), (2) training in the production and application of biofertilizer, (3) field demonstrations and participatory action research (80% practice), and (4) evaluation of farmers’ understanding, enthusiasm, and the impact on crop yield. The results showed improved farmer knowledge and skills in processing organic waste into biofertilizer, enhanced soil fertility, and increased sweet corn productivity. This activity also raised awareness among farmers about the importance of environmentally friendly and sustainable agricultural practices.